Reducing Dependence on Chemical Pesticides: Effectiveness of Vegetable Pesticides from Papaya Leaf Extract Against Plant Pests - Zulfania, Refi; Pangestu, Angger Arya; Sabrina, Dela Citra; Qurotaa’yun, Mutia; Maulana, Rifka Nazar; Fridansia, Keflin; Adinda, Restu; Aldillano, Rafi; Anissa, Siti Nur; Setyowati, Khaila Dwi; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to evaluate the level of adoption of farmers towards the use of vegetable pesticides made from papaya leaves in controlling plant pests. In addition, this study also aims to analyze the effectiveness and assess the application of these vegetable pesticides as an environmentally friendly alternative compared to the use of chemical pesticides. Through this approach, it is hoped that a deeper understanding of the potential of papaya leaves can be obtained as a sustainable and safe pest control solution for the environment and human health. The research method used in the study of pesticides or vegetable fertilizers made from papaya leaves was carried out through experimental approaches and field surveys. This study used purposive sampling method, which is the deliberate selection of respondents based on certain criteria relevant to the study objectives. The approach used in this activity included three main stages: (1) counseling on the concept and benefits of vegetable pesticides as an environmentally friendly alternative in pest control; (2) technical training to farmers on how to make vegetable pesticides based on natural ingredients, especially papaya leaves; and (3) direct field assistance in the application process of vegetable pesticides, to ensure proper application in accordance with the principles of sustainable agriculture. Through this approach, it is expected to increase farmers’ knowledge, skills and confidence in using vegetable pesticides independently and effectively.